Early detection of extended high frequency sensorineural hearing loss in chronic suppurative otitis media using extended high frequency pure tone audiometry - Ali, Ahmad Hafiz (2018)
Objective : The relationship between chronic suppurative otitis media with sensorineural hearing loss is still debatable. The availability of extended high frequency pure tone audiometry evaluation makes the detection of extended high frequency sensorineural hearing loss possible at much earlier stage. Thus, the aim for this study is to look for the prevalence of extended high frequency sensorineural hearing loss in chronic suppurative otitis media and the association between duration of the disease with extended high frequency sensorineural hearing loss. Design : One hundred and twenty chronic suppurative otitis media ears and one hundred and twenty normal ears for control group who never have history of ear problem before were enrolled in this study. All participants age 11 till 50 years old, who previously had a normal bone conduction threshold using conventional pure tone audiometry (frequency 250Hz. 500Hz, 1kHz, 2kHz, 4kHz and 8kHz) underwent examination using otoscopy, microscope and extended high frequency pure tone audiometry evaluation. Extended high frequency pure tone audiometry evaluation at frequency 9kHz, 10kHz, 11.2kHz, 12.5kHz, 14kHz and 16kHz were done in a sound proof cabin, which is located in a sound treated room. The average hearing threshold of all extended high frequencies will be taken as degree of hearing loss. Any hearing threshold at 25dB or more were taken as present of extended high frequency sensorineural hearing loss, following World Health Organization degree of hearing loss. The degree of extended high frequency sensorineural hearing loss will be graded into normal, mild, moderate, moderately severe, severe and profound. Data were analyzed using SPSS version 22 and STATA version 11.0.Result : Prevalence of extended high frequency sensorineural hearing loss in chronic suppurative otitis media group were 78.3% and in control group were 26.2%. There was a highly significant association between chronic suppurative otitis media, patient’s age and duration of the disease with extended frequency sensorineural hearing loss (p-value < 0.001). Result also showed the longer the duration of chronic suppurative otitis media, the more severe the degree of extended high frequency sensorineural hearing loss. Conclusion: Extended high frequency audiometry test is very useful in detecting early extended high frequency sensorineural hearing loss in chronic suppurative otitis media. This test should be regularly done in chronic suppurative otitis media cases to prevent further worsening of the irreversible sensorineural hearing loss and early prevention can be taken.